Interleukin-8 Induces the Endothelial Cell Migration through the Activation of Phosphoinositide 3-Kinase-Rac1/RhoA Pathway - Lai, Yi (Ivyspring International Publisher, 2011)
Endothelial cell migration is essential for tumor angiogenesis, and interleukin-8 (IL-8) has been shown to play an important role in tumor growth, angiogenesis, and metastasis. This study aimed to investigate the molecular mechanism of IL-8 induced endothelial cell migration. Our results indicated that IL-8 induced a rapid rearrangement of the actin cytoskeleton in EA.Hy926 cells, generating extensions resembling membrane ruffling and stress fibers. These processes required parallel upregulation of the small GTPases Rac1 and RhoA. Moreover, we demonstrated that IL-8 activated PI3K following the same kinetics observed from IL-8 induction of cytoskeletal rearrangement, suggesting the participation of PI3K in these processes. Taken together, our study demonstrates that PI3K-Rac1/RhoA signaling pathway plays a vital role in IL-8 induced endothelial cell migration, and provides new insight into the molecular mechanisms by which IL-8 contributes to tumor angiogenesis and metastasis.